The effects of vitamin D, C, E and zinc supplementation in chronic non specific low back pain - Unal Mehmet; Gulcelik Ertunc Gonul; Sezgin Burak Ahmet; Kocaturk Muammer (Open Journal of Pain Medicine - Peertechz Publications, 2021)
Objective: We aimed to investigate the effects of vitamin D3, vitamin C, vitamin E and zinc supplements on pain and functional capacity in Chronic Low Back Pain (CLBP). Methods: 20 patients (female/male:10/10) with CLBLP, aged between 28 and 57 years (mean age: 41.25±9.12), participated in the study. Mcgill Pain Questionnaire (MPQ) was used to measure the state of pain. Pain-related functional capacity was evaluated through Roland Morris Disability Questionnaire (RMDQ). Fear-Avoidance Beliefs Questionnaire (FABQ) used to assess fear-avoiding beliefs based on physical activity and the effects of work in chronic low back pain. The Finger Floor Test (FFT)used to assess the flexibility of trunk flexion. Evaluations were performed before and after treatment.  Result: Before treatment; the mean of MPQ was 50,55±6,03, the mean of FFT was 5,5±2,35 cm, the mean of RMDQ was 14,9±2,38, the mean of FABQ was 50,7±5,68. After treatment; the mean of MPQ was 23,45±5,35, the mean of FFT was 2,45±0,89 cm, the mean of RMDQ was 6,95±1,70, the mean of FABQ was 22,5±5,73. The results were statistically significant difference between before and after assesment scores (p<0,05). Conclusion: Vitamin D, C, E and zinc have been found to be effective in the treatment of patients with chronic low back pain.